Mekanisme Denda Yang Adil Dalam Pembiayaan Akad Bai' Bitsman Ajil: Perspektif Ekonomi Islam - Andi Bisyriani; Zulfahry Abuhasmy (Mappideceng:Jurnal Ekonomi Syariah, 2024)
Bai' Bithaman Ajil (BBA) is one of the financing instruments widelyapplied in the Islamic financial system, where buyers purchasegoods with deferred payments in the form of installments. Despiteoffering a flexible financing alternative, the main challenge in theimplementation of BBA contracts is a fair penalty mechanism,especially in the context of late payments by debtors. This researchaims to explore a penalty mechanism that complies with Islamiceconomic principles, focusing on fairness, transparency, andavoiding usury. In Islamic economics, fines must be compensatory,proportionate, and not become an additional burden that harms thedebtor. A fair fine mechanism must also pay attention to flexibilityfor customers experiencing economic difficulties, and avoidexploitation practices. This research uses a literature reviewapproach and systematic analysis of relevant literature, with the aimof formulating policies that support more inclusive and equitableIslamic financing practices. The results show that the application offines in BBA must consider the principles of justice, transparency,and the principle of rahmah in Islam, in order to create a balancebetween rights and obligations, and maintain social welfare. Theimplementation of a fair penalty mechanism is not only important toensure contract compliance, but also to create trust between Islamicfinancial institutions and customers